To improve the ASTM standard of residual stress measurement via central hole drilling process by incorporating the effects of hole eccentricity - Bahiran Adnan (2019)
The aim of this Final Year Project (FYP) is improve on the existing American Society for Testing and Materials (ASTM) standard E837 – 13a titled ‘Standard Test Method for Determining Residual Stresses by the Hole-Drilling Strain-Gage Method’. The improvement to be implemented will be by incorporating the effects hole eccentricity into the calculation of residual stress. In this report, the various methods for eccentricity correction in Hole-Drilling Strain-Gage Method will be analysed. Using MATLAB software, two codes are to be produced and compared its validity against the results produced by current existing commercial software. The first MATLAB code will be based on the ASTM Standard Method which does not consider the effects of hole eccentricity. The second will be an improvement of the ASTM Standard Method that will reduce errors caused by hole eccentricity. The results obtained from the code is then tested for its accuracy and validity. This is done by obtaining the residual stress values of the three sources mentioned above and plotting the values against hole depth increments for comparison and analysis.